Digitalization, Investment, and Education Level as Determinants of Digital Transformation in ASEAN - Shedriko, Shedriko; Subiyantoro, Heru; Rozali, M (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2025)
Purpose – This research aims to further examine the social and cultural connections of communities in ASEAN countries to digital transformation. Methodology/approach – This research uses Positivism Methodology applied descriptively and verifiably, using data obtained from the World Bank and UNDP over a period of 10 years, from 2014 – 2023.Findings – It was found that the variables of high-speed internet, fixed telephone density, educational level, and the grouping of the ratio of the number of mobile phones to users showed a significant value from the research conducted. Meanwhile, the cellular phone user variable without grouping, ICT service exports, foreign direct investment both with or without grouping, and the level of education with grouping by years of schooling did not provide significant values in this study.Novelty/value – Communities in ASEAN countries that have social and cultural habits with high appreciation and interest in technology, thus using more than 1 mobile phone per person, can accelerate digital transformation in these countries.